Distribuição das tensões em overdentures mandibulares em função do número de implantes e tipo de conexão quando submetidos a carregamento oclusal: análise fotoelástica e extensométrica - Borges, Anna Clara Mendes [UNESP] (2017)
The consensus statement recommends at least two implants to support a mandibular overdenture for edentulous patients. However, to reduce cost and time of treatment, the concept of single implant-retained overdentures provides another option. Nonetheless, the optimal number of implants required to retain a mandibular overdenture is still under evaluation. The objective of this study was to evaluate the biomechanical behavior of overdentures supported by 1 or 2 implants with different types of connections and submitted to compression, by photoelastic analysis (PA) and strain gauge analysis (SGA). Based on a cast of an edentulous mandible, the specimens were divided in 4 groups of 1 specimen each for the PA and 4 groups of 5 specimens each for the SGA, divided by the type of connection (Morse taper and external hexagon) and the number of implants (1 or 2). For PA, the photoelastic implant/prosthesis cast assembly was positioned in a circular polariscope associated with a universal testing machine (EMIC) and applying compression. The tension generated was photographed and analyzed qualitatively. For SGA, 2 strain gauges were positioned on the mesial and distal of each implant and the electrical signals were captured by a data acquisition device (ASD2001). The data were submitted to ANOVA and the Bonferroni test (P<0.0001) Through PA, the greatest number of tension fringes in both connection types was presented by the two- implant supported overdentures when compared with the single-implant supported overdentures. Through SGA, a statistical difference was verified between the connections in groups with 1 implant (P<0.0001), with the Morse taper having the lowest microstrain values. The lowest tension values in both types of connections were presented by the overdentures with 1 implant (P<0.0001). It was concluded that the number of implants directly influenced the distribution of tension in both forms...